PERSEPSI GURU TENTANG PENGAMBILAN KEPUTUSAN YANG DILAKUKAN OLEH KEPALA SEKOLAH DI SEKOLAH MENENGAH KEJURUAN NEGERI 2 PADANG - Ayang Mustika Sari (Universitas Negeri Padang, 2015)
The purpose of this research is to study how teacher’sperceptions of the decision made by the principal at the high school vocational 2 Padang. This research is the study population, with a sample of 73 teacher’s. This research instrument using statements with Likert scale models that have been tested. Data were analyzed through average. the results showed that teacher’sperceptions of the decision made by the principal at the high school vocational 2 Padang still in enough categories.Keywords : DecisionMaking by the Principal